Blow up of Coupled Nonlinear Klein-Gordon System with Distributed Delay, Strong Damping, and Source Terms. (14th September 2020) - Ouchenane, Djamel; Boulaaras, Salah Mahmoud; Alharbi, Asma; Cherif, Bahri
Abstract : This present work deals with the blow up of the coupled Klein-Gordon system with strong damping, distributed delay, and source terms, under suitable conditions.